Examining firearm-related deaths in Mexico, 2015-2022 - Eugenio Weigend Vargas; Michelle Degli Esposti; Stephen Hargarten; Laura Vargas; Jason E. Goldstick (BMC, 2024)
Abstract Background Globally, Mexico is one of six countries with the highest level of firearm mortality. While previous studies have examined firearm mortality in Mexico before 2015, increases in violence since then highlight the need for an updated analysis. In this study, we examined changes in firearm-related deaths in Mexico from 2015 to 2022 and described these deaths by key demographic groups, incident location, and state of occurrence. Data came from Mexico's Instituto Nacional de Estadistica y Geografia (INEGI), a federal agency that collects and reports national population data. We used descriptive statistics to analyze rates, proportions, and percentage changes in firearm mortality, and we displayed temporal trends using time plots and special trends using maps. Results Firearm deaths increased in Mexico from 2015 to 2018 but slightly decreased from 2018 to 2022. Homicides presented the highest increase and the highest proportion of firearm-related deaths from 2015 to 2022. Victims were primarily males but rates among women increased at a higher proportion (99.5% vs 53.5%). One third of victims were 20-29y but rates among children and adolescents (10-9y) increased at a higher proportion. Most firearm-related deaths occurred in streets or public spaces but the percentage of incidents occurring in households have increased. State-level rates and percentage changes varied significantly. States with higher rates of firearm mortality coincide with those involving conflict among organized criminal organizations. Conclusion Firearm mortality in Mexico is a major public health burden. The epidemiology of firearm-related deaths in Mexico varies by intent, demographics, location, and states. To mitigate this challenge, multiple solutions are required.